2003
DOI: 10.1046/j.1365-313x.2003.01888.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of two functional phosphoenolpyruvate/phosphate translocator (PPT) genes in ArabidopsisAtPPT1 may be involved in the provision of signals for correct mesophyll development

Abstract: SummaryThe Arabidopsis thaliana chlorophyll a/b-binding protein underexpressed 1 (cue1) mutant shows a reticulate leaf phenotype and is defective in a plastidic phosphoenolpyruvate (PEP)/phosphate translocator (AtPPT1). A functional AtPPT1 providing plastids with PEP for the shikimate pathway is therefore essential for correct leaf development. The Arabidopsis genome contains a second PPT gene, AtPPT2. Both transporters share similar substrate speci®cities and are therefore able to transport PEP into plastids.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
147
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(151 citation statements)
references
References 53 publications
4
147
0
Order By: Relevance
“…Consistently we observed that the PEP/P i translocator (PPT), located in the inner chloroplast envelope membrane, accumulated with a low BS/M ratio of 0.21 (TC286421). PPT homologues in Arabidopsis were shown to be expressed specifically in the mesophyll cells (PPT1) or veins (PPT2) and are required for formation of mesophyll tissue (124).…”
Section: Purification Of M and Bs Chloroplast Membranes Frommentioning
confidence: 99%
“…Consistently we observed that the PEP/P i translocator (PPT), located in the inner chloroplast envelope membrane, accumulated with a low BS/M ratio of 0.21 (TC286421). PPT homologues in Arabidopsis were shown to be expressed specifically in the mesophyll cells (PPT1) or veins (PPT2) and are required for formation of mesophyll tissue (124).…”
Section: Purification Of M and Bs Chloroplast Membranes Frommentioning
confidence: 99%
“…PPT genes are expressed at low levels in various tissues (Knappe et al, 2003b). To determine the expression pattern of GspPTs, semiquantitative reverse transcription-PCR was used.…”
Section: Gsgptmentioning
confidence: 99%
“…Import of phosphoenolpyruvic acid (PEP) from the cytosol by the PEP/phosphate transporter (PPT) drives fatty acid biosynthesis and synthesis of compounds by the shikimate pathway (i.e. aromatic amino acids; Fischer et al, 1997;Knappe et al, 2003b;Voll et al, 2003) and a Glc-6-P/phosphate transporter (GPT) provides Glc-6-P for starch synthesis in heterotrophic plastids (Kammerer et al, 1998;Niewiadomski et al, 2005). Last, a protein closely related to the GPT, the pentose-P/phosphate transporter (XPT), connects the oxidative pentose-P pathways (OPPPs) in cytosol and plastid (Eicks et al, 2002;Flü gge and Gao, 2005).…”
mentioning
confidence: 99%
“…Transformants were selected with kanamycin and verified by PCR analysis. Histochemical localization of GUS activity was performed as described previously [19].…”
Section: Plant Transformation and Gene Expression Analysismentioning
confidence: 99%